People's Republic of China : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This staff report on People's Republic of China 2013 Article IV Consultation highlights macroeconomic developments and outlook. China has maintained robust growth since the global crisis, but the heavy reliance on credit and investment to sustain activity is raising vulnerabilities. The consequence is a steady build-up of leverage that is eroding the strength of the financial sector, local government, and corporate balance sheets. This is most apparent in the continued rapid expansion in total social financing. The development of nontraditional finance marks a shift to more market-based intermediation, and the migration of activity to less-regulated parts of the system poses risks to financial stability.